Análise, projeto e implementação de um inversor trifásico baseado no conversor CC-CC Buck-Boost - Melo, Vinicius Secchin de (2020)
Knowledge of the soil water retention curve (SWRC) and the hydraulic conductivity curve (HCC) is important in understanding the behavior of unsaturated soils. The called pedotransfer functions (PTFs) are used to transform easy to measure data, such as the soil particle size distribution, into data that are difficult to measure, such as SWRC and HCC. This dissertation investigates the influence of the particle size distribution and textural classes on the SWRC and the HCC of a hydrophysical database of Brazilian soils. The equation proposed by van Genuchten (1980) is adopted to define the SWRC and HCC curves of these soils. The experimental data were separated according to three classifications: (a) classification in 10 subgroups based on the percentage of fines (Fc), (b) classification in 5 textural classes based on the textural triangle called FAO (Food and Agriculture Organization of the United Nations) and (c) classification in 12 textural classes based on the USDA (United States Department of Agriculture) textural triangle. The analyzes were compared with results obtained in the literature for temperate soils. The results suggest that the influence of Fc is not observed in the adjustment parameters of the van Genuchten equation (1980) for soils with Fc> 10% for HYBRAS soils and Fc> 30% for UNSODA soils. These parameters should not be interpreted as having physical meaning. The influence of the soil particle size distribution on saturated hydraulic conductivity and HCC is limited for the three investigated classifications. In general, the information limited on the soil particle size distribution is not enough to describe the variability of SWRC and HCC for the soils investigated in this research. It is recommended caution in the use of PTFs for soils different from those used to define these mathematical functions